P-010 Practice variations in addressing acute tandem carotid occlusions in emergent large vessel occlusion strokes. (23rd July 2017) - Coffman, S; Trott, S; Alhajeri, A; Fraser, J
Abstract : Introduction/Purpose: There are, at present, no standardized clinical practice guidelines addressing the endovascular management of acute ischemic stroke attributable to tandem occlusive disease (cervical carotid occlusion with intracranial large vessel occlusion). We conducted a systematic review of available literature, as well as reviewed cases from our own institution, in order to identify current practice variants, and highlight neurointerventional approaches that are most frequently utilized. Materials and Methods: We conducted a retrospective review of patients with acute ischemic stroke secondary to a tandem occlusion (intracranial occlusion with concomitant extracranial steno-occlusive carotid disease) that were treated with emergent thrombectomy from July 1, 2011 to December 31, 2015 at the University of Kentucky. Clinical (age, gender, stroke risk factors, NIHSS at admission), radiographic (distribution of intracranial occlusion), and interventional (recanalization technique for extra- and intracranial steno-occlusive disease, peri- and post-operative anti-coagulation/anti-platelet, and time to recanalization) data were collected. Using the PubMed database, we conducted a review of available literature from ?January 1, 2011 through February 28, 2017 on the endovascular treatment of tandem occlusions, extracting the same clinical, radiographic, and interventional data when available. Results: 29 studies (Mean age: 65.2; Mean NIHSS on admission: 15.7) were included. 28 (97%) carried out acute stent-assisted recanalization of the cervical ICA, with 25 (89%) using adjunctive angioplasty. 18 (64%) of these favored the proximal-to-distal approach. 13 (45%) utilized systemic heparinization. 7 (24%) utilized general anesthesia for all cases, 6 for majority (21%), and 3 (10%) for some (no distribution given). Loading doses (LD) of aspirin and clopidogrel were given before stenting in 7 (24%) and post-procedure in 2 (7%). Aspirin alone before stenting was used in 3 (10%) and after in 6 (21%), with 5 of these 9 giving clopidogrel LD post-procedure. 5 (17%) reported peri-procedural GPIIb/IIIa inhibitors. 19 (68%) addressed maintenance antiplatelet regimens, all using aspirin and clopidogrel. For our institution, 10 patients (Mean age: 60, Mean NIHSS at admission: 16.3) were included. 4 underwent acute stenting (50% proximal-to-distal approach); 2 underwent angioplasty alone, 2 underwent thromboaspiration alone, and 2 underwent IA tPA alone. 1 case used systemic heparinization. General anesthesia was used in 5 patients. 2 received aspirin LD and 1 aspirin and clopidogrel LD post-procedure. 3 discharged on aspirin and clopidogrel, 2 on aspirin alone. Conclusion: For tandem occlusions with cervical ICA involvement, acute stenting with adjunctive angioplasty, is a current prevailing practice for recanalization of the extracranial ICA. There is considerable variability in antiplatelet protocols, with a slight favoring of the administration of loading doses of aspirin and clopidogrel before stent deployment. Variability is also present for anesthesia, with general anesthesia having a significant role. Disclosures: S. Coffman: None. S. Trott: None. A. Alhajeri: None. J. Fraser: None.